2020
DOI: 10.3389/fimmu.2020.00042
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of γδ T Cell Effector Diversification in the Thymus

Abstract: γδ T cells are the first T cell lineage to develop in the thymus and take up residence in a wide variety of tissues where they can provide fast, innate-like sources of effector cytokines for barrier defense. In contrast to conventional αβ T cells that egress the thymus as naïve cells, γδ T cells can be programmed for effector function during development in the thymus. Understanding the molecular mechanisms that determine γδ T cell effector fate is of great interest due to the widespread tissue distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 114 publications
2
68
0
Order By: Relevance
“…The ability of remaining iNKT cells to produce high levels of IL-17 suggest that iNKT17 cells could contribute to airway inflammation, as described ( 18 ), and AHR observed in NOD mice. It is noteworthy that both iNKT and Vγ1 + T cells, in contrast to conventional CD4 + T cells, do not recognize peptides ( 33 35 ). These ILT cells can promptly produce cytokines following TCR-dependent or -independent activation ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of remaining iNKT cells to produce high levels of IL-17 suggest that iNKT17 cells could contribute to airway inflammation, as described ( 18 ), and AHR observed in NOD mice. It is noteworthy that both iNKT and Vγ1 + T cells, in contrast to conventional CD4 + T cells, do not recognize peptides ( 33 35 ). These ILT cells can promptly produce cytokines following TCR-dependent or -independent activation ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the development of several waves of γδ T cell subsets, such as Vγ5Vδ1 + dendritic epidermal T cells (DETCs) or Vγ6Vδ1 + IL-17-producing γδ T cells, exclusively takes place in the fetal thymus and these cells are maintained as long-lived effector cells after birth [23,24]. Early ontogenetic murine γδ T cell subsets are characterized by the expression of highly invariant and public TCRs that are shared among individual mice [55].…”
Section: γδ T Cell Subsets Arise Early During Ontogenymentioning
confidence: 99%
“…In contrast, Vγ7 + T cells reside as specialized intraepithelial lymphocytes in the gut, and Vγ1 + T cells circulate as naïve or IFN-γ-committed T cells in the periphery. Furthermore, IL-17-producing Vγ4 + or Vγ6 + T cells are enriched in tissues such as the dermis, oral mucosa, brain, joints or reproductive tracts [23,24]. Similarly, human γδ T cells can be roughly grouped by V-gene usage (Table 1).…”
mentioning
confidence: 99%
“…The pattern of YFP positivity, marking cells that have experienced T-bet expression, recapitulates previous knowledge of T-bet function. For example, the expression of T-bet in developing NKT cells and γδ T cells in the thymus (58)(59)(60)(61). It has previously been reported that IFNγ-producing γδ T cells express T-bet and IL-17A producing γδ T cells express RORγt (60).…”
Section: Discussionmentioning
confidence: 99%